Effects of ramadan fasting on cardiovascular and biochemical parameters - Gupta, M; Khajuria, V; Akhter, P (Indian Journal of Community Health, 2013)
Background: Muslims abstain from food and drink from dawn to sunset every day during Ramadan - the holiest month in Islamic lunar calendar. Methods: The effect of Ramadan fast on body mass index (BMI), blood pressure (BP), fasting blood glucose (FBG) and lipid profile were studied on 100 healthy male, adult Muslim volunteers. All parameters were recorded one week before the onset and then in the last week of Ramadan month and compared. Results: There was no statistically significant effect on BMI, and systolic or diastolic blood pressures (p>0.05). However, fasting blood glucose (FBG), serum total cholesterol (TC), serum triglycerides (TG) were significantly decreased (p = 0.000) and high density lipoprotein cholesterol (HDL-C) level was significantly (p=0.000) increased in last week of Ramadan fasting compared to pre fasting levels. Conclusion: Our results show beneficial effects of Ramadan fasting on FBG and serum lipid profile.